Plant and Animal-Type Feedstuff Shape the Gut Microbiota and Metabolic Processes of the Chinese Mitten Crab Eriocheir sinensis - Chen, Xiaowen; Lu, Deyin; Li, Zhihua; Yue, Wucheng; Wang, Jun; Jiang, Xiaoyan; Han, Hua; Wang, Chenghui (Frontiers in Veterinary Science, 2021)
In animals, growth and development are strongly correlated with the gut microbiota and metabolic profiles. In this study, gut microbiome communities, metabolic profiles, and growth performance of Eriocheir sinensis under three dietary feed types based on waterweed plants only, freshwater snails only, and waterweed plants combined with freshwater snails were studied by using 16S rRNA gene sequencing and liquid chromatography-mass spectrometry. Results indicated that different feed types dramatically affected the growth performances of E. sinensis by altering the gut microbiota and metabolic profiles. Aquatic plants, such as waterweeds, played essential roles in shaping gut microbiome communities, and the optimal Bacteroides-to-Firmicutes ratio might strongly promote growth performance. Waterweed plants also helped decrease maleficent Proteobacteria caused by excess animal-type feedstuff, such as freshwater snails, and might have positive roles in antibacterial functions in gut. A diet based on waterweeds only resulted in lipid metabolism disorders, which significantly retarded the growth of E. sinensis. In summary, E. sinensis cultured with a diet of waterweeds and freshwater snails showed superior growth performance due to their healthy gut microbiota and metabolic homeostasis. Our findings unveiled the roles of aquatic plants and animal-type food such as freshwater snail in shaping the gut microbiota and metabolic processes and provided guidance for the aquaculture of E. sinensis in future.